Cementless bipolar hemiarthroplasty for displaced fracture neck of femur with modular hydroxyapatite coated stem in elderly with cardiopulmonary co-morbidities - Bhat, Towseef Ahmad; Ali, Zameer; Gulzar, Amara; Mirza, Furqaan (International Journal of Research in Medical Sciences, 2017)
Background: Bipolar hemiarthroplasty is one of the common procedures done for fracture neck of femur in elderly. Debate about Cemented or cementless is still on. Cementing increases perioperative mortality by causing significant hemodynamic changes or embolization. Patients with cardiopulmonary complications are at higher risk of cementing complications. We report our series of 31 cases of fracture neck of femur with cardiopulmonary diseases operated over 2 years with modular cementless bipolar hemiarthroplasty. Methods: 31 elderly patients with cardiopulmonary co-morbidities (age=75 to 97 years) with displaced femoral neck fractures were operated between January 2011 to December 2013. Cementless bipolar hemiarthroplasty using hydroxyapatite coated stem was done by single surgeon using same implant in all the patients through anterolateral approach. Clinical and radiological follow-up was done with mean follow up of 54 months (36-72 months). Results: Total 31 cases with cardiopulmonary comorbidities were operated. The average follow up was 54 months. No intraoperative mortality was seen. 3 patients had splitting of femur during canal preparation. 1 patient died due to cardiac arrest in the post-operative period. 1 patient had surgical site infection. 3 patients had hemodynamic abnormalities and 1 patient had significant limb length discripency (1.5 cm). 2 patients died in the follow up because of comorbidities. 27 patients reached to pre-injury status with average harris hip score of 86 at final follow up. Conclusions: Cementless bipolar hemiarthroplasty with hydroxyapatite coated stem is a good option for femoral neck fractures in elderly patients with cardiopulmonary complications without risking the harmful effects of cementing.